International firms' economic nationalism and trade policies in the globalization era - Chandan, Harish C., 1947-; Christiansen, Bryan, 1960- (Business Science Reference, 2019)
"This book provides an understanding of the recent rise of the economic nationalism in the context of the hyper connected global economy. Strategies for the managers of the domestic and international firms will be discussed to make their firms successful"--